Outsourcing is so passé. (Economist, 2012)
The article discusses outsourcing in the computing industry as of June 2012, focusing on the transfer of technical support and call centres to locations such as the Philippines and India, as well as the emergence of unsourcing which involves the development of Internet-based peer-to-peer support networks by corporations. The use of social networking websites such as Facebook and Twitter is also mentioned.